(untitled) (Research, Society and Development, 2020)
Objective: to describe the practice of Permanent Education (PE) as a tool in the managerial work process of nurses in the context of primary care. Method: descriptive research with a qualitative approach, conducted with nurses from two community clinics of the family in the city of Niterói - Rio de Janeiro. For data collection, semi-structured interviews and audio recording were performed. The thematic content analysis technique was used. The research was approved with the opinion of the Research Ethics Committee (REC), under CAAE nº 64840416.3.0000.5243 of Federal Fluminense University. Results: after analyzing the data, the following categories emerged: Permanent Education as a management strategy for nurses at Community Family Clinics and challenges of Permanent Education as a strategy for renewing management in the nurse’s work process. Conclusion: contributions from the use of permanent education were found in teamwork and in the management of nurses in Community Family Clinics, enabling the transformation in their work environment, in addition to the obstacles that can hinder this process.